2019
DOI: 10.1016/j.adolescence.2019.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation, identity distress, and internalizing symptoms among resettled adolescent refugees

Abstract: Introduction: This study examines the relations among native and host country acculturation, identity distress, and internalizing symptoms among multicultural adolescent refugees (N = 33) resettled to the United States from a range of countries including Cuba, Iraq, Jordan, Haiti, Colombia, and Venezuela. Despite previous research supporting the advantages of developing a bicultural style to acculturation, mixed results have been found regarding native and host country acculturation patterns among resettled re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 44 publications
0
9
2
Order By: Relevance
“…Our findings contrast prior research that attributes immigrant health disparities to acculturation without attention to larger contexts of discrimination (Guler & Berman, 2019; Salant & Lauderdale, 2003). While culture and the process of acculturation are related to health, they are defined by the larger structures and systems that they operate within.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings contrast prior research that attributes immigrant health disparities to acculturation without attention to larger contexts of discrimination (Guler & Berman, 2019; Salant & Lauderdale, 2003). While culture and the process of acculturation are related to health, they are defined by the larger structures and systems that they operate within.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with previous research (Guler, 2014;Penner et al, 2019), we found no significant effect of indirect victimization or sexual victimization on identity formation. Furthermore, maltreatment was associated with identity synthesis only.…”
Section: The Role Of Childhood Adversity In Identity Formation During...contrasting
confidence: 99%
“…To promote youth's health, migrant settlement organizations and communities needs to create environments that encourage youth to identify with and maintain ties with their native culture. The organizations need to support youth to establish stable social support systems (e.g., friendships or strong family ties) and focus on training programs that support youth's sense of identity, mental health and wellbeing [53].…”
Section: Discussionmentioning
confidence: 99%